Combining the Grisotti flap with a secondary dermoglandular pedicle for partial breast reconstruction following contiguous central-inferior segment breast cancer excision. Issue 1 (1st January 2021) - Malata, Charles M.; See, Isabel Jia Le; Kazzazi, Fawz; Forouhi, Parto; Di Pace, Bruno
Abstract: A 61-year-old patient (38DD) with multifocal invasive ductal carcinomas requested breast-conserving surgery. An innovative two pedicle combination using a laterally-based Grisotti flap and an inferomedially-based secondary pedicle was designed to reconstruct a combined central breast (NAC included) and inferior segment resection defect. Satisfactory cosmesis with clear resection margins was achieved.